KAJIAN YURIDIS TERHADAP PUTUSAN MAHKAMAH KONSTITUSI TENTANG SENGKETA KEWENANGAN LEMBAGA NEGARA YANG KEWENANGANNYA DIBERIKAN UUD TAHUN 1945 - Muzayanah (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The authority of state institutions granted by the 1945 Constitution often experiences problems due to the emergence of different interpretations of the issue of authority between one state institution and the authority of other state institutions. Disputes on the authority of state institutions occurred in Indonesia which resulted in delays in the implementation of the authorities held by state institutions that were given and regulated in the 1945 Constitution. Disputes on the Authority of State Institutions (SKLN) related to Presidential Decree (Keppres) of the Republic of Indonesia Number 105/P of 2021 concerning Dismissal Acting Governor of South Kalimantan and Ratification of the Appointment of the Governor and Deputy Governor of South Kalimantan. The lawsuit filed is related to the application filed on September 16, 2021 which was received at the Registrar's Office of the Constitutional Court on September 17, 2021 based on the Deed of Submission of the Petitioner's Application Number 02/SKLN/PAN.MK/AP3/10/2021 and recorded in the Electronic Constitutional Case Registration Book (e-BRPK) with Number 2/SKLN-XIX/2021 on October 26, 2021, submitted by a person named Khairil Anwar. Mr. Khairil Anwar basically asked that Presidential Decree No. 105/P/2021 be revoked, stating the reason that at the time of the inauguration of the Governor and Deputy Governor of South Kalimantan, Br. Khairil Anwar is in the process of submitting an application for the General Election Results Dispute (PHPU) for the Governor of South Kalimantan Election at the Constitutional Court (MK), namely Case Number 151/PHP.GUB-XIX/2021 which has been registered with the Constitutional Court which is still in process and officially registered with Online Number 42/PAN.Online/2021 dated August 25, 2021, 10:44 WIB, exactly 2 Hours 46 Minutes before the scheduled inauguration at 13.30 on the same day. The Court is of the opinion that Mr. Khairil Anwar did not meet the requirements to file a case and was asked to study the MK's procedural law first in litigation at the MK. In the case submitted, Mr. Khaliril Anwar is not one of the state institutions mentioned in the 1945 Constitution as a party that can litigate. Then the problem in this research is whether Mr. ? This study uses a case approach and legislation. The method of analysis in this research is descriptive analysis. The results of the study describe that the Constitutional Court with the Constitutional Court Decision Number: 2/SKLN-XIX/2021 gave the decision not to accept the lawsuit filed by Br. Khairil Anwar with the verdict read out in the trial of the Constitutional Court.